Desenho do espaço construtivo, a Arte do Relacionamento. Elemento e estrutura na forma e significado dos espaços urbanos Porto. - Rui Américo Branco da Silva Cardoso (2016)
From the mid-twentieth century, the transformation of cities occurs at a rate which greatly differs from the rate of transformation that occurred in the past. Cities grow quickly, and generally follow concepts and models which are universal and insensible to their own physical and cultural realities. The adoption of generalist and quantitative urban regulation, not taking the specific morphological and typological values into account, causes distortion and disqualification of urban structures. This fact is particularly striking in cities that, being the result of a historical process of development that gives them a special environmental character, are subjected to interventions that mischaracterize their structures and urban spaces. Although we identify the need for enlarged urban reality's recognition and qualification, consisting of rural array territories overlapped with mobility infrastructure and dispersion of activities, which are characteristics that inhibit us to recognize it as city and as urban architecture; in this work we focus the look at consolidated or in consolidation contexts, convinced that the protection and enhancement of these contexts, will greatly contribute to the balanced modelling of that expanded urban reality. Each city has its own urban matrix witch is expressed in its urban structures. As a result of their development process in time, cities are realities with morphological diversity. The city is an entity composed of successive extracts and forms that determine different urban environments. This diversity is also reflected in the diversity or urban character and is a qualifying factor of the city. Only the recognition, characterization and optimization of the urban structure - expression of diversity shaped into urban forms built by appropriation, urbanization and construction processes - can contribute to the unity and qualification of the city as an entity that brings together the diversity and authenticity of its constituent parts. Considering that the city approach strategy is the key to the establishment of a city idea/project, we proceed to the selection and analysis of a set of texts on the city's approach strategies, with particular focus on the approaches developed in the second half of the twentieth century, and we pursue a thematic matrix to framework those strategies. In this work, taking as a physical reference the built space of Oporto, we value the importance of the complementarity between the historical, physiographic and spatial recognition of urban structures, thus enhancing the time of the built space, the morphology of the built space and the materiality of the built space, to establish specific methodological principles that can better inform the urban transformation processes.